The Role of Teachers in Developing Student Work Programs in School Organizations at SMP IT Fitrah Hanniah - Vinka Aurelia Zahwa; Sayan Suryana; Saprialman Saprialman (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study aims to analyze the role of teachers in developing student work programs within school organizations at SMP IT Fitrah Hanniah. The study used a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The research informants consisted of the vice principal for student affairs, the teacher accompanying the organization, and student members of BEST (Integrated Student Executive Board). Data were analyzed using Miles and Huberman's analysis techniques through data reduction, data presentation, and conclusion drawing. The results show that teachers play a crucial role as facilitators, guides, motivators, and evaluators in supporting the success of student work programs. Teachers not only assist in the implementation of organizational activities but also instill the values of character, leadership, social responsibility, and cooperation in students. Regular evaluation and active collaboration between teachers and students are important factors in maintaining the sustainability of the organization's work programs. Obstacles identified include unequal student involvement and limited funding for activities. However, these obstacles can be overcome through intensive teacher mentoring and optimization of school facilities. This study confirms that active teacher involvement in student organizations can support the holistic development of student character and potential based on Islamic values.